Visualization of xylem embolism by X‐ray microtomography: a direct test against hydraulic measurements. Issue 2 (14th February 2017) - Nolf, Markus; Lopez, Rosana; Peters, Jennifer M. R.; Flavel, Richard J.; Koloadin, Leah S.; Young, Iain M.; Choat, Brendan
Summary: X‐ray microtomography (microCT) is becoming a valuable noninvasive tool for advancing our understanding of plant–water relations. Laboratory‐based microCT systems are becoming more affordable and provide better access than synchrotron facilities. However, some systems come at the cost of comparably lower signal quality and spatial resolution than synchrotron facilities. In this study, we evaluated laboratory‐based X‐ray microCT imaging as a tool to nondestructively analyse hydraulic vulnerability to drought‐induced embolism in a woody plant species. We analysed the vulnerability to drought‐induced embolism of benchtop‐dehydrated Eucalyptus camaldulensis plants using microCT and hydraulic flow measurements on the same sample material, allowing us to directly compare the two methods. Additionally, we developed a quantitative procedure to improve microCT image analysis at limited resolution and accurately measure vessel lumens. Hydraulic measurements matched closely with microCT imaging of the current‐year growth ring, with similar hydraulic conductivity and loss of conductivity due to xylem embolism. Optimized thresholding of vessel lumens during image analysis, based on a physiologically meaningful parameter (theoretical conductivity), allowed us to overcome common potential constraints of some lab‐based systems. Our results indicate that estimates of vulnerability to embolism provided by microCT visualization agree well with those obtained from hydraulic measurements on the same sample material.